EFFECTIVE WAYS OF APPLYING THREE APPROACHES OF ENGLISH LANGUAGE TEACHIN - Madaminova Gulbahor Husniddin qizi; Maxkamova Munisxon Abdumannopovna, Sarsenbayeva Nargiza Maxset qizi (Journals Park Publishing, 2023)
As we know, in modern teaching of foreign languages new methods and approaches are becoming compulsory to make the process of studying faster and effective. In this article has been discussed the merits of three language methods and the role of these approaches in a foreign language while studying it.
Keywords: techniques, methods, Grammar-translation method, Total Physical Response, The communicative method, strategies.